2022
DOI: 10.1093/bioinformatics/btac432
|View full text |Cite
|
Sign up to set email alerts
|

PScL-DDCFPred: an ensemble deep learning-based approach for characterizing multiclass subcellular localization of human proteins from bioimage data

Abstract: Motivation Characterization of protein subcellular localization has become an important and long-standing task in bioinformatics and computational biology, which provides valuable information for elucidating various cellular functions of proteins and guiding drug design. Results Here, we develop a novel bioimage-based computational approach, termed PScL-DDCFPred, to accurately predict protein subcellular localizations in huma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 46 publications
0
5
0
Order By: Relevance
“…In this section, to further illustrate the predictive power of PScL-2LSAESM, we performed experiments and compared its performance with that of the other existing protein subcellular localization predictors including PScL-DDCFPred ( Ullah et al , 2022 ), PScL-HDeep ( Ullah et al , 2021 ), SAE-RF ( Liu et al , 2020 ), SC-PSorter ( Shao et al , 2016 ) as well as the method proposed by Yang et al (2014) .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…In this section, to further illustrate the predictive power of PScL-2LSAESM, we performed experiments and compared its performance with that of the other existing protein subcellular localization predictors including PScL-DDCFPred ( Ullah et al , 2022 ), PScL-HDeep ( Ullah et al , 2021 ), SAE-RF ( Liu et al , 2020 ), SC-PSorter ( Shao et al , 2016 ) as well as the method proposed by Yang et al (2014) .…”
Section: Resultsmentioning
confidence: 99%
“…These included SLFs, LBP, CLBP, LETRIST and RICLBP with the dimensionalities of 840, 256, 906, 413 and 408, respectively. Previous studies have shown these features to be very effective in this field ( Ullah et al , 2021 , 2022 ; Xu et al , 2016 ). SLFs are the global features which includes 4-dimensional DNA distribution and 836-dimensional Haralick texture features ( Boland and Murphy, 2001 ; Ullah et al , 2022 ; Xu et al , 2013 ).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…In comparison with conventional intelligence method, deep learning is able to perform a series of target recognitions, feature extraction, and analysis automatically, which makes it possible to automatically discover image–target features and explore feature levels and interaction ( Chen et al, 2016 ; Siu et al, 2020 ; Ullah et al, 2021 ; Li et al, 2022 ). The learning-enhanced cell optical image-analysis model is capable of acquiring the texture details from low-level source images and achieve higher resolution improvement for the label-free cell optical-imaging techniques ( Chen et al, 2016 ; Lee et al, 2020 ; Ullah et al, 2021 ; Ullah et al, 2022 ). The deep-learning pipeline of cell optical microscopy imaging can extract complex data representation in a hierarchical way, which is helpful to find hidden cell structures from the microscope images, such as the size of a single cell, the number of cells in a given area, the thickness of the cell wall, the spatial distribution between cells, and subcellular components and their densities ( Boslaugh and Watters, 2008 ; Donovan-Maiye et al, 2018 ; Falk et al, 2019 ; Manifold et al, 2019 ; Rezatofighi et al, 2019 ; Yao et al, 2019 ; Zhang et al, 2019 ; Lee et al, 2020 ; Voronin et al, 2020 ; Zhang et al, 2020 ; Chen et al, 2021a ; Gomariz et al, 2021 ; Manifold et al, 2021 ; Wang et al, 2022b ; Islam et al, 2022 ; Kim et al, 2022 ; Melanthota et al, 2022 ; Rahman et al, 2022 ; Ullah et al, 2022 ; Witmer and Bhanu, 2022 ).…”
Section: Introductionmentioning
confidence: 99%